A Characteristic Mapping Method for Vlasov-Poisson with Extreme Resolution Properties (Communications in Computational Physics, 2024)
We propose an efficient semi-Lagrangian characteristic mapping method forsolving the one+one-dimensional Vlasov-Poisson equations with high precision on acoarse grid. The flow map is evolved numerically and exponential resolution in linear time is obtained. Global third-order convergence in space and time is shown andconservation properties are assessed. For benchmarking, we consider linear and nonlinear Landau damping and the two-stream instability. We compare the results with aFourier pseudo-spectral method and results from the literature. The extreme fine-scaleresolution features are illustrated showing the method’s capabilities to efficiently treatfilamentation in fusion plasma simulations.
Keywords: Characteristic mapping method; kinetic equations; Vlasov-Poisson; plasma.